The Role of Volition in Organizational Learning: The Case of Automotive Product Recalls - Haunschild, Pamela R.; Rhee, Mooweon (Management Science, 2004)
What is the role of volition in organizational learning? Do firms learn better in response to internal procedures or external mandates? Existing literature provides conflicting answers to this question, with some theories suggesting that volition is important for learning because autonomy increases commitment and problem analyses, whereas external mandates tend to produce defensive reactions that are not coupled to the organization in any useful way. Yet, other theories suggest that mandate is important for learning because external pressures act as jolts that help overcome organizational inertia, resulting in deep exploration of problems to prevent future surprises. We investigate this issue in the context of automakers learning from voluntary versus involuntary product recalls. Using data on all recalls experienced by automakers that sold passenger cars in the United States during the 1966–1999 period, we follow the learning-curve tradition in investigating the effects of voluntary and involuntary recalls on subsequent recall rates. We find that voluntary recalls result in more learning than mandated recalls when learning is measured as a reduction in subsequent involuntary recalls. This effect is at least partly because of shallower learning processes that result from involuntary recalls. The effect of volition, however, is different for generalist and specialist automakers. The results of this study suggest an important, yet understudied, determinant of the rate and effectiveness of learning—volition. The results also add to our knowledge of the different learning processes of generalist and specialist organizations.